PENINGKATAN PENGETAHUAN REMAJA PUTRI TENTANG PENCEGAHAN ANEMIA MELALUI KEGIATAN SOSIALISASI KESEHATAN - Dhiya Urrahman; Hernawan Isnugroho; Pritta Yunitasari; Nur Cahya Rachmawati (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2024)
Anemia is a common health problem among adolescent girls and may affect physical health, academic performance, and quality of life. Limited knowledge and awareness regarding anemia and its prevention contribute to the high prevalence of anemia in this group. This community service activity aimed to improve the knowledge and awareness of adolescent girls regarding anemia prevention through health education activities. The program was conducted in Sawahan 5, Gunung Kidul Regency, involving 30 adolescent girls. The method applied was face-to-face health education through lectures, discussions, and question-and-answer sessions using presentation media and leaflets. Evaluation was carried out using pre-test and post-test to assess changes in participants’ knowledge levels. The results showed an increase in knowledge after the education program, indicated by an improvement in the good knowledge category from 20.0% to 66.7% and a decrease in the poor knowledge category. These findings indicate that health education and socialization activities are effective in increasing adolescent girls’ understanding of anemia and its prevention and may support the adoption of healthy behaviors from an early age.